Carbonation reaction of recycled concrete aggregates (RCA): CO2 mass consumption under various treatment conditions - Hossein Sousanabadi Farahani; Amin Hosseini Zadeh; Jiong Hu; Chris Hawkins; Seunghee Kim (Cleaner Materials)
Concrete is a key building material around the world due to its excellent strength and durability. Recycling demolished concrete for new construction materials may play a significant role in sustainable development. Producing recycled concrete aggregates (RCA) from waste concrete is one approach for such an initiative. However, using RCA may pose challenges, such as reduced density, lower elastic modulus and strength, and increased water absorption. Recently, the carbonation of RCA has emerged as a method to address those concerns. This study explores the carbon sequestration capacity of RCA through carbonation, examining various parametric conditions, including initial CO2 pressure, relative humidity, temperature, and pre-treatment approach. Both lab-scale and large-scale carbonation tests were conducted. Additionally, a cost analysis and CO2 footprint assessment were performed. The findings showed that applying higher initial CO2 pressures (e.g., 40–60 psi) and optimal relative humidity (∼55 %) could significantly enhance the carbonation efficiency of RCA. Elevating temperature also led to accelerated CO2 consumption, being more effective on the lab scale. The economic analysis presented potential cost benefits when substituting natural aggregates with CO2-treated RCA. All in all, these results suggest that the carbonation of RCA may provide significant environmental benefits through carbon sequestration, promoting sustainable construction practices.